Common goods – research methodology (Economic and Political Thought, 2014)
The basic aim of the article is to systemise the typology of common goods.The concept of common goods, although in use for a long time and researchedinto a number of times, is not interpreted unequivocally. Researchers preferanalysing the mechanisms of particular common goods to looking for commonbasis for defining common goods described in literature. Moreover, theconducted analysis of the phenomenon places common goods in the classicgoods classification, gives an insight into additional criteria narrowing theconcept of the common good, and creates the basis for formulating a dynamicdefinition of the common good according to the level of the good saturationwith features thought to be the key ones for the concept.